PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBANTUAN SMART APPS CREATOR PADA MATERI DAERAHKU DAN KEKAYAAN ALAM - Wardah Latipah; Ratih Purnamasari; Fitri Anjaswuri (STKIP Subang, 2026)
This study aims to produce interactive multimedia media products assisted by Smart Apps Creator on the material of my region and natural resources of class IV-B at SDN Baranangsiang with 20 students. This product development uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research begins with making observations first, obtained from observations, interviews, questionnaires, and documentation whose results are processed through qualitative data analysis techniques and quantitative data. Validation was carried out by media experts, language experts, and material experts and the trial was conducted on 20 students of class IV-B SDN Baranangsiang. The results of media validation that have been carried out obtained a percentage of 94%, language validation 92%, and material validation of lecturers and teachers 96% so that in total the overall average obtained a percentage of 94.5% with the criteria “very feasible”. While the results of the study, the researcher concluded that multimedia using the smart apps creator application on the material of my region and natural resources was ‘'very feasible’' to be used in learning activities.